Peran Teknologi 5G dalam Mendorong Pertumbuhan Ekonomi Digital dan Transformasi Industri - Endang Supriatna; Muh. Zulfi Qadri; Evan Haviana; Ahmad Dani; Andi Naila Quin Azisah Alisyahbana (CV. ULIL ALBAB CORP, 2024)
5G technology has taken center stage in efforts to drive digital economic growth and industrial transformation around the world. This research focuses on Bandung, Indonesia, as the study site, to investigate the role of 5G technology in the context of a large, growing city. The research method utilizes a mixed approach, combining quantitative surveys with in-depth interviews to gain comprehensive insights. The analysis results show that while the adoption of 5G technology is increasing, challenges such as high investment costs and infrastructure limitations remain barriers. However, the perceived positive impacts, such as increased operational efficiency and innovation, demonstrate the significant potential of this technology. The importance of awareness, education, regulatory support, and cooperation between stakeholders was highlighted as key in creating an enabling environment for the growth of 5G technology. Practical measures, including infrastructure investment and the establishment of an inter-stakeholder forum, are suggested to accelerate Bandung's digital transformation and make the most of 5G technology's potential.